The Effect Of Economic Variables And Personality Towards Subjective Well-Being: The Moderating Effect Of Job Satisfaction - Yekta, Zeinab Amini (2017)
The study aims to identify if both economic variables and personality has a significant relationship with subjective well-being. In addition, this study intends to investigate if job satisfaction moderates the relationship between economic variables, personality and subjective well-being. Atotal 590 of questionnaires were distributed to cement companies,and471 questionnaire was completed and returned, which most of them (85.4 percent) were male. The results showed that mostly personality dispositions were significantly related to subjective well-being and economic variables just partially related to life satisfaction.